Polıcy For Governance Of Balı Fermented And Dıstılled Beverages As An Effort To Improve The Welfare Of Farmers Of Karangasem Dıstrıct: (Study of Bali Governor Regulation No. 1 of 2020 in increasing the production of Balinese arak in Sibetan Village, Uangdem District) - Toto Noerasto; A.A. Ayu Dewi Larantika; I Made Mardika; I Made Sanjaya; Ni Putu Dinda Kalpika Putri; Ni Luh Sephia Adnyani Putri (Cita Konsultindo Research Center, 2024)
The issuance of Bali Governor's Regulation Number 1 of 2020 concerning the Management of Balinese Fermented and/or Distilled Drinks, which aims to build production standardization to ensure the safety and legality of fermented and/or distilled beverage products, especially Balinese, while preserving the community's ritualistic traditions related to the use of arak. in religious activities. This research aims to analyze the policy of Bali Gubernatorial Regulation No. 1 of 2020 and reviewing the effectiveness of implementation regarding efforts to improve the welfare of farming communities. This descriptive qualitative research uses an ethnographic approach, which examines a group of farming communities with distinctive ethnicities in Sibetan Village, Bebandem District, Karanganyar Regency. Data was collected through interviews and discussions as well as literacy, which was then carried out interpretive analysis. The research results show that Bali Governor Regulation no. 1 of 2020 is running effectively, as evidenced by the community's willingness to utilize and process agricultural products into Balinese arak products of good quality and become export commodities, followed by fulfilling administrative requirements in accordance with laws and regulations regarding alcoholic beverages. The existence of this regulation has been proven to be able to improve the economic welfare of the community, which is also proven by the establishment of cooperatives and collaboration with several companies and turning traditional Balinese wine into an export commodity.